Selected temporal, grammatical, and phonological characteristics of conversational utterances produced by children who stutter. - Logan KJ; Conture EG (Journal of Speech, Language & Hearing Research, 1997)
The purpose of this study was to assess clause, syllable, and response latency characteristics of conversational utterances produced by children who stutter. Subjects were 14 boys who stutter (M age = 52.07 months; SD = 9.02 months) and 14 boys who do not stutter (M age = 51.93 months; SD = 8.55 months). Selected aspects of speech fluency, clause and syllable structure, and response latency were analyzed in utterances collected from each subject as he spoke with his mother during a 30-minute conversation. Results indicated that stuttered utterances of children who stutter contained significantly more clausal constituents than their length-matched fluent utterances. There was, however, no significant difference in syllable structure of the length-matched utterances, and neither stuttering frequency nor duration was significantly associated with syllable structure measures. Further, there was no significant difference in response latency of non-length-matched stuttered and fluent utterances. Findings are taken to suggest that changes in the number of clausal constituents that must be constructed, stored, or coordinated within an utterance may influence the likelihood of speech errors and, hence speech disfluencies within that utterance.